2018
DOI: 10.1002/ejlt.201800107
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Green and Conventional Extraction Methods on Lipid Yield and Fatty Acid Profiles of Fish Species

Abstract: The efficiency of the green extraction methods ultrasound‐assisted extraction (UAE) and microwave‐assisted extraction (MAE), and conventional methods (Soxhlet and Bligh and Dyer), on lipid content and fatty acid profiles of six fish species (Mullus barbatus, red mullet; Upeneus moluccensis, goldband goatfish; Mullus surmuletus, surmullet; Anguilla anguilla, European eel; Pagellus erythrinus, common pandora, and Saurida undosquamis, brushtooth lizardfish) are evaluated. The results of lipid content of fish spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
(89 reference statements)
2
18
1
Order By: Relevance
“…Modified Bligh and Dyer extraction using chloroform and methanol as solvents was used as a reference extraction method [21]. The changes made to the original method were: centrifugation at 4500 rpm for 10 min, and the solvent layers were evaporated with a rotary evaporator.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…Modified Bligh and Dyer extraction using chloroform and methanol as solvents was used as a reference extraction method [21]. The changes made to the original method were: centrifugation at 4500 rpm for 10 min, and the solvent layers were evaporated with a rotary evaporator.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…The difference between months is thought to accumulate DHA found to increase gradually in the body by getting used to the ambient conditions during the stay in the same bay in this fish, which is a migratory species. Seafood contains high and balanced amounts of polyunsaturated fatty acids, especially EPA and DHA (Lunn and Theobald 2006;Ozogul et al 2009Ozogul et al , 2018. Both EPA and DHA are known to be important for human health (Cooner 2000).…”
Section: Table 2-fatty Acids (Mg/100g) Composition Of Narrow-barred Spanish Mackerelmentioning
confidence: 99%
“…Although, Dal Bosco et al (2019) reported similar results value for stearic acid, Tanakol et al (1999) and Yavuzer (2020) found higher results values of the amounts of palmitic acid and stearic acid in sand smelt from the Marmara Sea (27.1 -7.0%) and Hirfanlı Dam, Turkey (26.85-6.40%), respectively. The fatty acid profile of fish species is not constant and it changes according to many morphological and ecological factors such as species, season, life stage, location, diet, and age of the fish, which have effects on the nutrient composition of fish and even vary broadly within species and among species (Lunn and Theobald 2006;Ozogul et al 2018).…”
Section: Saturated Fatty Acids (Sfa)mentioning
confidence: 99%